Analysis and reconstruction of laser printer information leakages in the media of electromagnetic radiation, power, and signal lines. Issue 58 (May 2016) - Ulaş, Cihan; Aşık, Ulaş; Karadeniz, Cantürk
Highlights: Compromising emanations of laser printers are analyzed in different media. New image patterns are proposed to identify leakage frequencies. The reconstruction procedure from electromagnetic emissions is explained. The method is analyzed in noisy and noiseless environments with four printers. Abstract: In this paper, the emissions of a laser printer are investigated in three media, which are electromagnetic radiation, power line conductors, and signal line conductors. Analysis of Compromising Emanations (CE) of printed data is divided into three parts. First, the candidate frequency points of CE are examined in the frequency domain. Second, the emitted signal is AM-demodulated with the proper bandwidth, and then sampled by a high storage oscilloscope in these frequency points. Third, the collected data are converted to 2 dimensional image by applying signal and image processing techniques. In addition, this study introduces some practical measurement methods to reveal the possible CEs of laser printers. Finally, the procedure of the image reconstruction of CEs of the laser printer data is explained in detail. Experimental studies are carried out in noisy and noiseless environment with four different printers and results show that the proposed method successfully identifies the CE frequency points.